Pengaruh Choi Siwon Pada Iklan Mie Sedaap Korean Terhadap Keputusan Pembelian Oleh Generasi Z - Naura Qurratu’aini; Siti Nursanti; Oky Oxcygentri (LUGAS Jurnal Komunikasi, 2021)
The entry of Korean culture in Indonesia has made many companies take steps to take advantage of this. Mie Sedaap is one of the instant noodle companies that saw this opportunity and took steps by releasing a new flavor variant, the Korean taste with Choi Siwon as its brand ambassador. This research was conducted to determine the extent of the influence arising from Choi Siwon in Mie Sedaap advertisement on the purchase decision of Generation Z on the basis of the theory of Stimulus Organism Response and Viscap Model which was carried out using quantitative methods, and by survey method, distributing questionnaires online to 360 respondents. which is obtained from calculations with the sampling technique, namely simple random sampling. The data analysis technique was performed using a Likert scale with simple linear regression equation data analysis. This study resulted in several things, namely that there was no influence between the visibility of Choi Siwon's brand ambassador on purchasing decisions, and there was an influence between credibility, attraction, and brand ambassador Choi Siwon's power on purchasing decisions